2013
DOI: 10.3390/ijms14011335
|View full text |Cite
|
Sign up to set email alerts
|

Potential Applications of Carbohydrases Immobilization in the Food Industry

Abstract: Carbohydrases find a wide application in industrial processes and products, mainly in the food industry. With these enzymes, it is possible to obtain different types of sugar syrups (viz. glucose, fructose and inverted sugar syrups), prebiotics (viz. galactooligossacharides and fructooligossacharides) and isomaltulose, which is an interesting sweetener substitute for sucrose to improve the sensory properties of juices and wines and to reduce lactose in milk. The most important carbohydrases to accomplish these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 157 publications
(180 reference statements)
1
42
0
Order By: Relevance
“…Also, immobilization enhances enzyme specificity and activity (Pollard et al, 2007;Woodley, 2008;Garcia-Galan et al, 2011), reduces the possibility of contamination by microbes (Singh, 2008), decreases the cost of continuous production, and improves purity of the final products (D'Souza, 1999). Indeed, studies of immobilized enzymes have advanced tremendously since Tosa et al (1967) first utilized immobilized aminoacylase to achieve continuous industrial production of L-amino acids in the 1960s (Tosa et al, 1967;Xie et al, 2009;Abdelmajeed et al, 2012;Vlakh et al, 2013;Contesini et al, 2013). In this study, we utilized DEAE-52 cellulose as the carrier to adsorb and immobilize puerarin glycosidase extracted from M. oxydans CGMCC 1788 to transform puerarin.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…Also, immobilization enhances enzyme specificity and activity (Pollard et al, 2007;Woodley, 2008;Garcia-Galan et al, 2011), reduces the possibility of contamination by microbes (Singh, 2008), decreases the cost of continuous production, and improves purity of the final products (D'Souza, 1999). Indeed, studies of immobilized enzymes have advanced tremendously since Tosa et al (1967) first utilized immobilized aminoacylase to achieve continuous industrial production of L-amino acids in the 1960s (Tosa et al, 1967;Xie et al, 2009;Abdelmajeed et al, 2012;Vlakh et al, 2013;Contesini et al, 2013). In this study, we utilized DEAE-52 cellulose as the carrier to adsorb and immobilize puerarin glycosidase extracted from M. oxydans CGMCC 1788 to transform puerarin.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…Different covalent immobilization strategies have been used to prepare stable and robust biocatalysts for use in the food industry (Husain, 2010;Contesini et al, 2013;Singh et al, 2011). For example, Barros et al (2003) have reported immobilization of cardosin A a plant protease that is present in aqueous extracts of thistle flowers (Cynara cardunculus) and have a history of use as rennets in cheesemaking (Lamas et al, 2001).…”
Section: Covalent Bindingmentioning
confidence: 99%
“…Several researchers have excellently and critically reviewed the importance and properties of glutaraldehyde in these applications 4,5 . Recent studies have demonstrated the utilization of glutaraldehyde pre-activated supports for imparting stability to various enzymes in food industry owing to their Generally Recognized as Safe status 6 .…”
Section: Introductionmentioning
confidence: 99%